Pathologic Findings of Chronic PML-IRIS in a Patient with Prolonged PML Survival Following Natalizumab Treatment. (September 2017) - Himedan, Mai; Camelo-Piragua, Sandra; Mills, Elizabeth A.; Gupta, Avneesh; Aburashed, Rany; Mao-Draayer, Yang
Immune reconstitution inflammatory syndrome (IRIS) is a common complication during treatment for natalizumab-associated progressive multifocal leukoencephalopathy (PML). Although severe IRIS can result in acute worsening of disability and is associated with poor prognosis, effective immune reconstitution may account for the high survival rate of this cohort of PML patients. We present pathological evidence of chronic IRIS 3.5 years after diagnosis with natalizumab-associated PML. Our case showed that the IRIS initially developed after plasma exchange therapy and resolved clinically and radiologically following a combination treatment with corticosteroids, maraviroc, and cidofovir. Autopsy 3.5 years later revealed evidence of grey-white matter junction demyelinating lesions characteristic of PML and perivascular leukocyte infiltrates predominated by CD8 + T-lymphocytes, and polymerase chain reaction analysis demonstrated the presence of JC viral DNA in this tissue, indicative of persistent PML-IRIS. While clinical symptoms of PML-IRIS typically stabilize within 6 months, our case report suggests that prolonged low-grade inflammation may persist in some patients. Better assays are needed to determine the prevalence of prolonged low-grade IRIS among PML survivors.